Metabolic profiling of Lolium perenne shows functional integration of metabolic responses to diverse subtoxic conditions of chemical stress - Serra, Anne-Antonella (J Exp Bot, 2015)
Plant communities are confronted with a great variety of environmental chemical stresses. Characterization of chemical stress in higher plants has often been focused on single or closely related stressors under acute exposure, or restricted to a selective number of molecular targets. In order to understand plant functioning under chemical stress conditions close to environmental pollution conditions, the C(3) grass Lolium perenne was subjected to a panel of different chemical stressors (pesticide, pesticide degradation compound, polycyclic aromatic hydrocarbon, and heavy metal) under conditions of seed-level or root-level subtoxic exposure. Physiological and metabolic profiling analysis on roots and shoots revealed that all of these subtoxic chemical stresses resulted in discrete physiological perturbations and complex metabolic shifts. These metabolic shifts involved stressor-specific effects, indicating multilevel mechanisms of action, such as the effects of glyphosate and its degradation product aminomethylphosphonic acid on quinate levels. They also involved major generic effects that linked all of the subtoxic chemical stresses with major modifications of nitrogen metabolism, especially affecting asparagine, and of photorespiration, especially affecting alanine and glycerate. Stress-related physiological effects and metabolic adjustments were shown to be integrated through a complex network of metabolic correlations converging on Asn, Leu, Ser, and glucose-6-phosphate, which could potentially be modulated by differential dynamics and interconversion of soluble sugars (sucrose, trehalose, fructose, and glucose). Underlying metabolic, regulatory, and signalling mechanisms linking these subtoxic chemical stresses with a generic impact on nitrogen metabolism and photorespiration are discussed in relation to carbohydrate and low-energy sensing.